2022
DOI: 10.1108/jsma-10-2021-0196
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of cross-country context effects on the link between green product strategy and financial performance

Abstract: PurposeDecades of research offer mixed results regarding the relationship between green product strategies and corporate financial performance. On the one hand, many scholars put forward green product strategies as a source of competitive advantage and in turn enhance financial performance. On the other hand, some studies suggest the opposite – that green product strategies may encounter managerial difficulties or are too costly, consequently leading to meager, if any, financial gain. This study explores cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…The general belief is that wealthier democratic countries, with wealthier populations, where there are strong environmental regulations and oversight are where green products and business strategies perform the best. Yet the findings of Kim et al (2022) show that perhaps the opposite is the case. They found that authoritarian governments boosted the financial performance of green corporations, largely through the use of targeted funding and the ability to act unilaterally to the financial benefit of local corporations.…”
Section: Customer Shiftsmentioning
confidence: 98%
See 1 more Smart Citation
“…The general belief is that wealthier democratic countries, with wealthier populations, where there are strong environmental regulations and oversight are where green products and business strategies perform the best. Yet the findings of Kim et al (2022) show that perhaps the opposite is the case. They found that authoritarian governments boosted the financial performance of green corporations, largely through the use of targeted funding and the ability to act unilaterally to the financial benefit of local corporations.…”
Section: Customer Shiftsmentioning
confidence: 98%
“…The work of Kim et al (2022) has looked at the impacts of stringent environmental regulators and regulations, consumer economic wealth, and democratic vs. authoritarian governments on the financial performance of green products and business strategies. The general belief is that wealthier democratic countries, with wealthier populations, where there are strong environmental regulations and oversight are where green products and business strategies perform the best.…”
Section: Customer Shiftsmentioning
confidence: 99%
“…Thus, NRBV provides a broader perspective by incorporating natural resources and environmental factors. It highlights how natural resources, which are integral to M&M companies' business, can provide both competitive advantage and addressal of environmental issues (Kim et al. , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…NRBV can help us understand how natural resources can drive both environmental challenges and competitive opportunities for firms in this sector (Menguc and Ozanne, 2005). By applying NRBV, we can gain valuable insights regarding the implementation of climate neutrality practices and the dynamics within the supply chain (Kim et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to the stakeholder theory, improving FP can result from efforts related to sustainability (Wahba, 2008). One of the management's goals in engaging sustainability initiatives may be to improve FP by luring stakeholders like customers, suppliers, and consumers to transact with the business (Al Amosh & Khatib, 2023) governments and staff (Kim et al, 2023; Menicucci & Paolucci, 2023). Introducing and applying the stakeholder theory is an effort to capture and analyze the larger context in which numerous interested parties are active.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%